Dextro-median hepatectomy for liver secondary cancer: 46 years after Hepatectomy of Caprio - Praderi, Raúl; Gómez Fossati, Carlos; Estefan, Alberto (Cirugía del Uruguay, 1978)
The authors point out that 46 years ago Dr. Gerardo Caprio report in this Surgical Society the first Regulated Hepatectomy published in the World literature. As a homenage to this author recently deceded they report what it seems to be the first national dextromedian hepatectomy for cancer with survival